ANALYSIS OF FINANCIAL STATEMENT PRESENTATION BASED ON SAK ETAP - Fitri Wulandari; Putri Puji Lukmawati; Silvia Rahmadi; Dafa Haikal (Sean Institute, 2023)
Financial statements result from an accounting process used for economic decision-making. However, only a few companies prepare financial reports according to established accounting standards for incomprehension or lack of knowledge to ensure reliable information. This study aimed to determine the presentation of financial statements based on the financial accounting standards of entities without public accountability (SAK ETAP) at PT Sentra Auto Motor. This research method is to use a qualitative descriptive method. The data collection technique used is documentation. The results of this study are that PT Sentra Auto Motor has presented financial statements in the form of profit and loss and balance sheet properly; the financial statements made can show the results of performance and asset position but have not fully implemented SAK ETAP, including not presenting comparatively, some accounts that at least according to SAK ETAP must be presented in the income statement and balance sheet, have not been presented by PT Sentra Auto Motor, and account grouping is not by SAK ETAP